Management and Outcomes of Ganglion Cysts of the Posterior Longitudinal Ligament: A Systematic Review of Diagnostic and Surgical Approaches - Scalia, Gianluca; Graziano, Francesca; Marrone, Salvatore; Ferini, Gianluca; Giurato, Eliana; Nicoletti, Giovanni Federico; Galvano, Gianluca; Umana, Giuseppe Emmanuele (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Ganglion cysts of the posterior longitudinal ligament (PLL) are a rare cause of lumbar radicular pain and claudication, primarily affecting young athletic males. These cysts are often linked to repetitive trauma and degenerative changes in the PLL, potentially aggravated by disc degeneration. Diagnosis is typically achieved through magnetic resonance imaging (MRI), with surgical excision being the preferred treatment in symptomatic cases. This systematic review consolidates the current knowledge on PLL ganglion cysts, examining clinical characteristics, diagnostic findings, and surgical outcomes to provide a basis for future research and clinical management.A systematic literature search was conducted in PubMed, Embase, Cochrane Library, and Web of Science, including studies from inception to June 2024. Search terms included “ganglion cyst,” “posterior longitudinal ligament,” “PLL,” and “lumbar spine,” among others. Studies published in English and French were reviewed if they reported on ganglion cysts of the PLL with clinical or radiological data. Data on demographics, symptoms, imaging findings, treatment approaches, outcomes, and follow-up were extracted. Due to the heterogeneity of the included studies, a narrative synthesis was performed, focusing on clinical presentation, diagnostic criteria, surgical techniques, and recurrence rates.A total of 14 studies comprising 20 patients were analyzed. The majority (90%) were male, with a mean age of 30.2 years (standard deviation [SD] = 11.47). The most common presenting symptom was radicular pain, primarily left-sided (70%). Disc degeneration was reported in 85% of cases, supporting a link between degenerative disc disease and PLL cyst formation. MRI revealed hypointense cysts on T1-weighted images and hyperintense on T2, aiding in differentiation from other intraspinal pathologies. Surgical excision was performed in all cases, with hemilaminectomy (50%) and interlaminar approaches (40%) being the most common techniques. Minimally invasive endoscopic methods were used in one case. Complete recovery was reported in 65% of patients, with a mean follow-up of 13.8 months (SD = 12.1). Recurrence data were limited due to inconsistent follow-up.This systematic review highlights the clinical and imaging characteristics of PLL ganglion cysts, with MRI as a critical tool for diagnosis. Surgical management, particularly hemilaminectomy and interlaminar approaches, is effective in providing symptom relief and preventing recurrence. Although minimally invasive techniques show promise, further research is needed to confirm their efficacy. Given the rarity of PLL cysts, tailored treatment and larger studies with standardized follow-up are essential to improve understanding and management of this condition.
Keywords: posterior longitudinal ligament; ganglion cyst; lumbar radiculopathy; MRI; surgery